(untitled) - P. Lakshmilavanya, Dr. B. Karuna, Rafi Shaik (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
India has been a land of articulate feelings, eloquent speeches and diverse manifestations; Indian drama comprises all the three. Kalidas, the undomitable, Bhavbhuti, the unimitable and Keshav, the unforgettable, are a few names that enhance this particular sensibility. As regards Indian English drama, it has assumed mythical stature due to its poor growth, right from its inception, as a sheer legacy to be proud of, K.R.S. Iyengar admits the fact while writing, "Modern Indian dramatic writing in English is neither rich in quantity nor, on the whole, of high quality. Enterprising Indians have for nearly a century occasionally attempted drama in English, but seldom for actual stage production."1 Going back to the days of launching of Indian English drama, like other genres, it is also imitative and derivative in nature, including translations from other languages, carrying forward its heritage with alien inclucations. Krishna Mohan Banerji is the beginner with his The Persecuted (1831), then came the flow of translations: Michael Madhusudan Dutta’s Ratnavali (1858), Sermista (1859) and Is This Called Civilization (1871) followed the corpus of Tagore, Sri Aurobindo and others modelled after the Elizabethan concept and structure, we may easily diagnose the encounter of two cultures (as in K.M. Banerji’s The Persecuted), at